2007
DOI: 10.1128/aem.01413-07
|View full text |Cite
|
Sign up to set email alerts
|

Novel Alphaproteobacterial Root Nodule Symbiont Associated with Lupinus texensis

Abstract: Phylogenetic analysis of rRNA gene, recA, nodA, nifD, and nifH sequences suggested that nitrogen-fixing symbionts from two populations of Lupinus texensis acquired the capacity for nodule symbiosis separately from other rhizobia in the alphaproteobacteria. Their closest 16S rRNA relatives were the nonsymbiotic taxa Chelatococcus, Bosea, and Balneomonas.Legume nodule symbionts are found in several lineages in the alphaproteobacteria and at least two lineages in the betaproteobacteria (5, 17). Four genera of alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Wiehe and Höflich (Wiehe and Höflich, 1995) previously reported that lupini plants were cultivated in the Müncheberg area. Lupini is nodulated by rhizobia belonging to the genus Bradyrhizobium (Eckhardt et al, 1931;Andam and Parker, 2007). A total of 28.6% isolates were assigned to the Rhizobium species in the present study.…”
Section: Phylogenetic Properties Of Isolatesmentioning
confidence: 65%
“…Wiehe and Höflich (Wiehe and Höflich, 1995) previously reported that lupini plants were cultivated in the Müncheberg area. Lupini is nodulated by rhizobia belonging to the genus Bradyrhizobium (Eckhardt et al, 1931;Andam and Parker, 2007). A total of 28.6% isolates were assigned to the Rhizobium species in the present study.…”
Section: Phylogenetic Properties Of Isolatesmentioning
confidence: 65%
“…OTUs 1401 and 2824 corresponded to the genera Bradyrhizobium (family Bradyrhizobiaceae ) and Microvirga (family Methylobacteriaceae ), both of them belonging to the order Rhizobiales , class Alphaproteobacteria , phylum Proteobacteria . The genus Bradyrhizobium comprises rhizobial species that develop symbiotic root nodules in legumes such as soybean ( Glycine max ) and peanut ( Arachis hypogaea ), while some Microvirga species establish a similar symbiotic process in the legumes Listia angolensis and Lupinus texensis (Andam & Parker, ; Ardley et al ., ). Another OTU (2474) assigned to the Bradyrhizobiaceae was detected in leaf endophytic samples and in low levels in the rhizosphere (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although a large number of lupine root nodule isolates from around the world has been characterized (6, 7, 9, 10, 12, 16, 42), only one example of nodulation by Microvirga has been reported, namely M. lupini from the North American L. texensis species (14,37). This appears to be a highly specific symbiosis, since no other Lupinus sp.…”
Section: Discussionmentioning
confidence: 99%